Epstein–Barr virus persistence and infection of autoreactive plasma cells in synovial lymphoid structures in rheumatoid arthritis. Issue 9 (25th December 2012) - Croia, Cristina; Serafini, Barbara; Bombardieri, Michele; Kelly, Stephen; Humby, Frances; Severa, Martina; Rizzo, Fabiana; Coccia, Eliana Marina; Migliorini, Paola; Aloisi, Francesca; Pitzalis, Costantino
Abstract : Objectives: Rheumatoid arthritis (RA) is associated with an increased Epstein–Barr virus (EBV) blood DNA load, a robust immune response to EBV and cross-reactive circulating antibodies to viral and self-antigens. However, the role of EBV in RA pathogenesis remains elusive. Here, we investigated the relationship between synovial EBV infection, ectopic lymphoid structures (ELS) and immunity to citrullinated self and EBV proteins. Methods: Latent and lytic EBV infection was investigated in 43 RA synovial tissues characterised for presence/absence of ELS and in 11 control osteoarthritis synovia using RT-PCR, in situ hybridisation and immunohistochemistry. Synovial production of anti-citrullinated protein (ACPA) and anti-citrullinated EBV peptide (VCP1/VCP2) antibodies was investigated in situ and in vivo in the severe combined immunodeficiency (SCID)/RA chimeric model. Results: EBV dysregulation was observed exclusively in ELS+ RA but not osteoarthritis (OA) synovia, as revealed by presence of EBV latent (LMP2A, EBV-encoded small RNA (EBER)) transcripts, EBER+ cells and immunoreactivity for EBV latent (LMP1, LMP2A) and lytic (BFRF1) antigens in ELS-associated B cells and plasma cells, respectively. Importantly, a large proportion of ACPA-producing plasma cells surrounding synovial germinal centres were infected with EBV. Furthermore, ELS-containing RA synovia transplanted into SCID mice supported production of ACPA and anti-VCP1/VCP2 antibodies. Analysis of CD4+ and CD8+ T-cell localisation and granzyme B expression suggests that EBV persistence in ELS-containing synovia may be favoured by exclusion of CD8+ T cells from B-cell follicles and impaired CD8-mediated cytotoxicity. Conclusions: We demonstrated active EBV infection within ELS in the RA synovium in association with local differentiation of ACPA-reactive B cells.